2015
DOI: 10.1016/j.anorl.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal preservation in ENT oncology. Retrospective series of 246 patients managed in the Caen University Hospital and François Baclesse Cancer Care Center between 1998 and 2008

Abstract: Over and above established criteria, the present study highlighted the importance of general health and nutritional status during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Although this factor was not significant in multivariate analysis for local failure in their study, it remained an independent predictor of ultimate local failure ( p = .023). This finding was further supported by Cuny et al who reported lower recurrence‐free survival for patients with WHO performance status >1. We identified WHO performance status >0 as an independent predictive factor for recurrence in general and for local recurrence in particular.…”
Section: Discussionsupporting
confidence: 69%
“…Although this factor was not significant in multivariate analysis for local failure in their study, it remained an independent predictor of ultimate local failure ( p = .023). This finding was further supported by Cuny et al who reported lower recurrence‐free survival for patients with WHO performance status >1. We identified WHO performance status >0 as an independent predictive factor for recurrence in general and for local recurrence in particular.…”
Section: Discussionsupporting
confidence: 69%
“…Last, noncancer and treatment-related deaths were higher in the concomitant arm. 9 Although there is no consensus in the literature 8,[12][13][14][15][16][17][18][19] about the optimal definition of OFPF, the definition used in the current study covers, in our opinion, all the relevant issues involved in functional outcomes of these patients. Furthermore, the data on predictive factors for OFPF are scarce and frequently conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…4,18e22 Additional confounding factors that may be recognized in the literature are the anatomical localization of the tumor (larynx, hypopharynx, oropharynx) and resectability of the tumor. 23 With TNM staging being revised in 2002 so as to restage former T2 tumors with involvement of the paraglottic space as T3, this became an additional parameter of heterogeneity among studies. Unfortunately, few of the studies which were running at the time, appear to have restaged their populations to meet the 6th edition of the International Union Against Cancer (UICC) TNM staging criteria and this has been proved to be a major exclusion criterion for this study.…”
Section: Populationmentioning
confidence: 99%